Stress hyperglycemia and electrolytes disturbance in patients with acute cerebrovascular stroke - Bastawy M. El-Fawal; Reda Badry; Wael A. Abbas; Ahmed K. Ibrahim (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2019)
Abstract Background Stroke is a medical emergency and considered the 2nd leading cause of mortality worldwide. High morbidity and mortality of stroke are due to some complications like cerebral edema, infection, and associated heart disease. Stroke may cause stress hyperglycemia and electrolyte disturbance that may be independent predictors for increased morbidity and mortality. Data on electrolyte disorder in neurological conditions especially acute stroke are somewhat scanty and not frequently interpreted. Objectives The current study aimed to evaluate the effect of stress induced by acute stroke on the blood glucose and serum electrolytes and its relationship to the type, severity, and prognosis of stroke. Subjects and methods A total of 100 patients admitted with acute stroke were included in the study. After informed consent, fasting blood sugar, glycosylated hemoglobin, serum sodium, and potassium levels were measured simultaneously. Stroke severity and outcome were assessed using the Glasgow Coma Scale. Results Stress hyperglycemia was noted in 21 patients, out of which 62% presented with hemorrhagic stroke. Undiagnosed diabetes was found in 47% of cases. Also, 13 % of our patients had both stress hyperglycemia and electrolyte disturbance simultaneously. Mortality among hemorrhagic versus ischemic patients was 46% and 22%, respectively. The independent predictors of mortality were stress hyperglycemia, electrolytes disturbance, ischemic heart diseases, and type and admission severity of stroke. Conclusion Stress hyperglycemia and electrolyte disturbance after acute stroke were found in 21% and 47% of patients respectively and may adversely affect outcome of stroke especially those with cerebral hemorrhage.